Nonflat time-variable dark energy cosmology - Pavlov, Anatoly; Westmoreland, Shawn; Saaidi, Khaled; Ratra, Bharat V. (My University, 2014)
We generalize the time-variable dark energy scalar field Φ model (ΦCDM) to nonflat space. We show that even in the space-curvature-dominated epoch the scalar field solution is a time-dependent fixed point or attractor, with scalar field energy density that grows relative to the energy density in spatial curvature. This is the first example of a physically consistent and complete model of dynamical dark energy in a nonflat geometry.
Keywords: Dark energy; Nonflat space